Les Pre-Requis A La Mise En Place D#x2019;une Politique De Ciblage D#x2019;inflation Au Maroc (Global Journal of Management and Business Research, 2019)
Faced with the failure of monetary policies inspired by Keynesian and monetarist thinking, a new pragmatic regime emerged in 1989, called inflation targeting. The new regime was able to bypass inflationary slippages in a short time, while promoting growth and employment, prompting central banks in some developed and emerging countries to adopt it and abandon previous monetary regimes. The adoption of inflation targeting requires, however, the verification of a set of pre-requisites. Morocco, like other countries, has failed in its monetary policy, since price stability has been ensured by the support of the State Budget, to certain products for consumption (Compensation Fund). With the increased partial decompensation, and in the event of a possible rise in commodity prices, inflation could reach very high levels. Therefore, Bank Al-Maghrib will be forced to revise its monetary policy to adopt the inflation targeting, as recommended by the IMF, but the verification of its prerequisites is necessary.
Keywords: monetary policy; inflation targeting; central bank; transparency; independence; credibility; flexible exchange rate regime